Argentina: Households and Labour Market Changes (2004-2009) - Groisman, Fernando Alberto (2011)
This article outlines the changes in employment between 2004 and 2009 and reviews the links that households establishedwith the labour market. An increase in the number of jobs registered withthe social security system was one of the key features of the period.Moreover, half of the rise in the observed employment rate representedjobs obtained by household members other than heads of household. Theincrease in protected employment also benefited social sectors that havetraditionally been neglected, although there are factors that restrict theaccess of certain population groups to such jobs. Another research findingis that if the head of the household has a protected job, other householdmembers have better chances of gaining a similar job themseselves.